Subtle tarsometatarsal ligament injury in a professional ballerina: weight-bearing computed tomography technical tip - Godoy-Santos, Alexandre Leme; Teixeira Lobo, Carlos Felipe; Rosemberg, Dov Lagus; Sposeto, Rafael Barban; Lintz, François; de Cesar Netto, Cesar (Journal of the Foot & Ankle, 2025)
Early detection of Lisfranc instability is critical for improving clinical outcomes, but diagnosing subtle injury can be challenging. Magnetic Resonance imaging associated with weight-bearing computed tomography (WBCT) allows evaluation of such injuries in 3 dimensions (3D) under physiologic load. This WBCT technical tip aimed to assess the utility of the 3D measurements between medial cuneiform and the base of the second metatarsal (C1-M2), between the medial and intermediate cuneiforms (C1-C2), and between the first and second metatarsals (M1-M2) to diagnose subtle injury in isolated ligamentous Lisfranc injuries. Level of evidence V, Therapeutic studies, Expert opinion.